Pelatihan Sistem Akuntansi untuk Meningkatkan Pemahaman Akuntansi bagi Guru Sekolah Menengah Kejuruan Yadika Bangil Pasuruan - Aulia Fuad Rahman; Tsabita Atina Silmi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
This Community Service Program was conducted to address the low level of accounting understanding among teachers at SMK Yadika Bangil, which affected the effectiveness of accounting instruction in the classroom. The main objective of this program was to enhance teachers’ competencies in understanding, organizing, and delivering accounting materials in a systematic, practical, and industry-relevant manner. The training methods included interactive lectures, group discussions, and simple case studies derived from real-world business accounting practices. The results of the program showed improvements in teachers’ understanding of basic accounting concepts, the stages of the accounting cycle, and the ability to prepare financial statements accurately. In addition, teachers were able to apply adjusting and reversing journal entries more precisely and relate the subject matter to actual industry practices. Teachers' active participation and enthusiasm throughout the sessions demonstrated the success of the applied training approach. This program is expected to improve the quality of accounting instruction and better prepare students to enter the workforce with stronger competence and professionalism.